2021
DOI: 10.1016/j.heliyon.2021.e08550
|View full text |Cite
|
Sign up to set email alerts
|

The effects of COVID-19 on livelihoods of rural households: South Wollo and Oromia Zones, Ethiopia

Abstract: Even though the COVID-19 pandemic is a global phenomenon that is heavily affecting the lives, livelihoods, and wellbeing of the entire population, the degree and severity of its effects are different among groups and sectors. In developing countries, where there is poor infrastructure coupled with a low level of education and a high incidence of poverty, the pandemic would result in increased unemployment, decreased income for daily labor, increased food insecurity, depletion of saving and relief measures, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
25
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 34 publications
5
25
2
Order By: Relevance
“…The COVID-19 pandemic is likely to have argumentative effects on agrarian households in Ethiopia. Smallholder farmers are one of the exposed groups who might be delayed from working on their land, getting into markets to sell their products, or buying seeds and other vital inputs [ 10 ]. In afar regional, state the first COVID-19 virus confirmed case was recorded on April 22, 2020.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic is likely to have argumentative effects on agrarian households in Ethiopia. Smallholder farmers are one of the exposed groups who might be delayed from working on their land, getting into markets to sell their products, or buying seeds and other vital inputs [ 10 ]. In afar regional, state the first COVID-19 virus confirmed case was recorded on April 22, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies [ 2 , 10 , 12 – 20 ] and so on a study on the macroeconomic impact of epidemic disease. Notwithstanding, most of the papers, including the above one were mainly focused on the macroeconomic effect of epidemic disease (like COVID-19), they did not give insight on the effect of COVID-19 on social and microeconomics effect (in general on social welfare), in addition, no studies addressed the regional wise social welfare effect of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Another similar study in Ethiopia, Malawi, Nigeria, and Uganda also found that 77% of the population lives in households were lost income as a result of this pandemic and public emergency 27 . Despite the lack of reporting on spatial distribution, one pocket study in Ethiopia also found that nearly 90% of households experienced non-resilience to food insecurity immediately after the occurrence of this pandemic disease and public emergency 5 , which was significantly higher prior to the occurrence of this pandemic and public emergency disease 28 – 37 . After COVID-19 was declared by WHO as a global health emergency and a pandemic disease, the efforts of humanitarian and food security organizations seeking to reverse food insecurity, resilience, and coping strategies were undermined 25 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the case fatality rate varies regardless of age, gender, ethnicity, socioeconomic status, or health status 3 . COVID-19 has now become a critical issue, exposing numerous associated problems such as panic and public anxiety throughout the population 4 , livelihood insecurity 5 , particularly food insecurity, and food crisis 6 . Food insecurity, in particular, is explained by the quantity and quality of available food, uncertainty about food accessibility, and personal experiences with going hungry during a public emergency 7 .…”
Section: Introductionmentioning
confidence: 99%
“…However, owing to the novel coronavirus disease (COVID- 19), livelihood security has been severely threatened in some countries [11][12][13][14]. For example, some people in Europe are losing access to their rightful education [13,15]; the pandemic has slowed economic development in many countries [16], incomes are declining, and employment has become precarious, with unemployment rates increasing in many countries and regions, including the EU28 and the US [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%